THE IMPORTANCE OF THE ACCESSIBILITY TO CELL THERAPY IN BRAZIL - Duarte, Fernando Barroso; Silla, Lúcia; Hamerschlak, Nelson (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
Editorial.